IMPLEMENTASI PROGRAM WATER, SANITATION, AND HYGIENE (WASH) OLEH UNITED NATIONS CHILDREN'S FUND (UNICEF) DI SULAWESI SELATAN - Simanjuntak, Christina Oktaviani; Olivia, Yessi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The problem of sanitation is an international problem, Indonesia is one of the developing countries that tend to lack knowledge about the importance of sanitation. Poor water sanitation, hygiene causes the death of 1.5 million toddlers due to diarrhea every year. To achieve universal access, Indonesia and the United Nations International Emergency Children's Fund (UNICEF) collaborate through the Water, Sanitation, and Hygien (WASH) Program to overcome sanitation problems in Indonesia and meet universal access targets. This research aims to explore UNICEF's implementation of the WASH program in addressing sanitation and clean water issues in South Sulawesi. The method used in this research is a qualitative method with primary data collection techniques, namely interviews with resource persons from UNICEF Indonesia and Makassar and secondary with document analysis. This research uses the role theory of international organizations. This theory is used to explain and affirm UNICEF in carrying out its roles based on the values set by international organizations. The results showed that the WASH program implemented by UNICEF in South Sulawesi succeeded in achieving Open Defecation Free (ODF) status in 2021, with the achievement of a decent sanitation target of 91.57% in accordance with the RPJMD and RPJMN. And an increase in safe sanitation of 6.14%. UNICEF plays an important role through policy advocacy, regulatory strengthening, technical assistance and community empowerment, while supporting the government in achieving sustainable sanitation targets in accordance with Sustainable Development Goal 6 Keywords: WASH, Sanitation, UNICEF, South Sulawesi, International Organization